The Pleasure and the Guilt - Impulse Purchase and Post Purchase Regret : A Study of Young Indian Consumers - Jain, Kokil; Gautam, Shalini; Pasricha, Diksha (Indian Journal of Marketing, 2018)
The main purpose of this research was to study and understand the factors that influenced the impulsive purchase behaviour in young Indian consumers and also the relationship it had with post purchase dissonance. The goal of this research was to examine the effect of the external factors as well as that of internal or individual factors on impulse purchase behaviour. The external factors studied included promotional activities (sales and coupons) and visual product aesthetics. The individual factors considered in this study are gender,Â hedonic shopping gratification, price consciousness, and consumer spending self-control. A structured questionnaire having established scales was utilized to measure the identified antecedents. Data were collected from students of post graduate courses of a university ; 241 responses were analyzed using SPSS 21 to test the results. This research was carried out in between April and May 2017. The dimensions which emerged as defining factors affecting impulse purchase in young Indian consumers were hedonic shopping gratification, sale proneness, visual product aesthetics, price consciousness, and consumer spending self-control. The results were not able to establish any significant relationship between gender and impulse purchase and coupon proneness and impulse purchase.